Desenvolvimento de tecnologia educacional para orientação nutricional em diabetes mellitus e hipertensão arterial para uso de agentes comunitários de saúde: uma revisão de escopo. - Sousa, Francisco Leonardo Teixeira de (2024)
Comorbidities in primary care require continuous and coordinated care. Technologies, such as monitoring applications and electronic medical records, support the management of these conditions and facilitate communication between professionals. Community health agents play a crucial role, acting in patient guidance, promoting self-care and using digital tools to record data, expedite referrals and strengthen the link between the community and the health system, improving access and efficiency of services. This research aims to model the fundamental contents of educational technology in the format of an application for use by CHWs in nutritional guidance work for patients with diabetes mellitus and arterial hypertension. Due to the broad nature of the research question, the protocol was prepared according to the scoping review methodology. Starting from the central question of the review, the eligibility criteria of the studies will be defined based on the domains of the Population, Concept and Context (PCC) strategy. Between April and October 2022, a systematic search was carried out in 7 electronic databases: PubMed, Scopus, Web of Science and in complementary and secondary databases. The search was structured by the keywords, DeCS (Health Sciences Descriptors) and MeSH (Medical Subject Headings) and the terms combined by Boolean operators. The process of selecting the studies and collecting and extracting the data was carried out by two reviewers independently, and discrepancies during the process were discussed and resolved by a third reviewer. The data were synthesized descriptively with categories that describe the characteristics of the publications retrieved in this review, in terms of population, context and concept, and main results mapped. After analyzing the 36 selected articles, it was found that only a small number (n=7) addressed the participation of Community Health Agents (CHAs) as protagonists of the research. Regarding the practice scenarios, 22.22% of the studies took place in PHC; regarding the care lines, 41.66% of the applications that worked on permanent care prevailed; the most prevalent comorbidities were diabetes mellitus (33.33%). Regarding nutritional approaches, nutritional guidelines prevailed (13.88%), and the most prevalent technological tools were mobile applications. Some limitations and potentialities were observed, but the study highlighted the importance of developing educational technologies aimed at nutritional guidance for patients with Diabetes Mellitus and Arterial Hypertension, especially in the context of the work of Community Health Agents (CHAs). In this context, I propose the development of a technology that can monitor and work on health education on a permanent basis, which would include the following fundamental functionalities and content: patient registration, alerts and reminders, health education, reports and follow-ups, and direct communication. The integration of educational technologies into the work of Community Health Agents is a promising strategy, constituting an important step in building more efficient and accessible health systems